Vitamin D Level and its Association with Mortality in Children Admitted in Pediatric ICU - Rizwana Qureshi, Bela Bashir, Tufail Ahmed Soomro, Muhammad Zaki, Mansoor Ahmed Bouk, Ghulam Rasool Bouk, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the relationship between the levels of vitamin D of pediatric ICU patients in Pakistan and its effect on the rate of mortality among them which will pave ways to improve the clinical outcomes among Pediatric ICU patients of Pakistan. Study Design: Prospective observational study. Place and Duration of Study: Pediatric Emergency Ward, Ghulam Muhammad Mahar Medical College, Sukkur Sindh Pakistan from 1st June 2018 to 31st December 2019. Methodology: Seven hundred and eighty two children of both genders and aged range 1 to 15 years were enrolled. There Vitamin D levels were taken at the time of admission. Results: The overall mortality rate was 13%. Mortality rate in sufficient group was ~9%. Mortality rate in insufficient group was up to 15% and in deficient group, it was 20.2%. The mortality rate was significantly higher in deficient and in insufficient group. Conclusions: Vitamin D levels are a significant predictor in the outcome of mortality in pediatric ICU. It is essential to monitor Vitamin D levels regularly, and efforts should be made to increase Vitamin D levels if they are deficient. Keywords: Vitamin D, Mortality, Pediatric ICU